Evaluation of post-harvest waste of coconut (Cocos nucifera L.) In Portoviejo, Tosagua and Rocafuerte, Manabi-Ecuador. (Revista Científica Ciencias Naturales y Ambientales, 2024)
The objective of this project was to carry out a socio-environmental evaluation of post-harvestcoconut waste in Portoviejo, Tosagua and Rocafuerte. The Participatory Rapid Diagnosis was usedin two stages: collection of information through surveys, sampling and technical visits to producingfarms, georeferencing of data and generation of proposals. The study determined that the mostplanted coconut variety was the giant (56%) with around 1 to 3 ha with between 500 to 800plants/ha, its production ranges between 800 to 1000 coconuts per harvest, whose residues aredisposed of to the collector. (46%), they burn (28%), and 74% of producers do not carry out goodenvironmental practices on their farms. Rocafuerte is the canton with the highest generation(96.31%), followed by Tosagua (2.64%) and Portoviejo with 1.05% of the total. It is necessary topromote the awareness of producers regarding the potential use of coconut waste under a circulareconomy approach.
Keywords: circular economy; production; environmental diagnosis